Cocaine Addiction and EEG in Infants - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Thirty-five consecutive infants of cocaine-addicted mothers hospitalized for a comprehensive health assessment and 51 healthy, age-matched infants were studied with electroencephalography at the Children's Hospital of Philadelphia, PA.